Interspeech 2018 2018
DOI: 10.21437/interspeech.2018-1849
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on Tonal Coarticulation in Continuous Speech

Abstract: Tonal variations in continuous speech are complicated in nature and it is a challenge to identify the effect of tonal coarticulation given several influencing factors. To address the issue, the present study proposes a scheme for labeling tonal coarticulation in Mandarin continuous speech by applying Hypo-and Hyper-articulation theory. We assume that the bidirectional tonal coarticulation (both carryover and anticipatory effects) as patterns of Hypo-articulation results from the economical articulatory rule. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Recall that only 27% of the AL word tokens in the congruent-cues condition carried tonal carryover assimilation. This percentage was rather low considering the percentage of bitonal sequences that showed a tonal coarticulatory effect (i.e., about 51%) as reported by Hao et al (2018) for Mandarin corpus speech. Therefore, an alternative view was that our listeners were unable to benefit from tonal carryover assimilation under the congruent-cues condition simply because it was not reliably present, not because it was redundant with TP information.…”
Section: Results and Discussion Of Experimentsmentioning
confidence: 70%
See 1 more Smart Citation
“…Recall that only 27% of the AL word tokens in the congruent-cues condition carried tonal carryover assimilation. This percentage was rather low considering the percentage of bitonal sequences that showed a tonal coarticulatory effect (i.e., about 51%) as reported by Hao et al (2018) for Mandarin corpus speech. Therefore, an alternative view was that our listeners were unable to benefit from tonal carryover assimilation under the congruent-cues condition simply because it was not reliably present, not because it was redundant with TP information.…”
Section: Results and Discussion Of Experimentsmentioning
confidence: 70%
“…Production experiments have revealed much evidence for tonal coarticulation in Mandarin and other lexical tone languages (see, e.g., Chen, 2012;Xu, 2001, for a review). Recently, Hao, Zhang, Xie, and Zhang (2018) proposed a scheme for annotating tonal coarticulation and applied it to speech samples from a Mandarin corpus. About 51% of bitonal syllable sequences in their data were labeled as being tonally coarticulated, suggesting that tonal coarticulation is prevalent in connected speech, at least in Mandarin.…”
Section: Tonal Coarticulationmentioning
confidence: 99%
“…However, Lin and Yan (1993) found that, in four-syllable words and phrases with typical stress pattern, tonal coarticulation was unidirectional: either carryover or anticipatory. Hao et al (2018) also showed that unidirectional and bidirectional effects coexist in continuous speech. Further, Lin and Yan (1993) found that the carryover/anticipatory coarticulation only affected the start/end points, without extending to the ends or starts of adjacent syllables.…”
Section: F0 Variation In Mandarin Tonal Coarticulationmentioning
confidence: 91%
“…In other words, there is both carryover and anticipatory coarticulation. Stronger carryover effects than anticipatory ones are found in the majority of the languages investigated; for example, Vietnamese (Han & Kim, 1974;Brunelle, 2003Brunelle, , 2009, Mandarin (Hao et al, 2018;Lin & Yan, 1993;Shen, 1990Shen, , 1992Xu, 1994Xu, , 1997, Taiwanese (Peng, 1997), Mizo (Dutta et al, 2017;Sarmah et al, 2015), Thai (Gandour et al, 1994;Potisuk et al, 1997), Tianjin Chinese (Li & Chen, 2016;Zhang & Liu, 2011), and Cantonese (Li et al, 2020). However, other languages show that the two effects are comparable, such that the carryover effects are no greater than the anticipatory ones; for example, Malaysian Hokkien (Chang & Hsieh, 2012), Nanjing Chinese (Chen et al, 2018), and Kinyarwanda (Flemming, 2011).…”
Section: Tone and Phonation Coarticulationmentioning
confidence: 95%
See 1 more Smart Citation